Design and Construction of a Constant Head Infiltrometer - Mahesh Bashyal; Michael J. Mulvaney; Eban Z. Bean (EDIS, 2019)
This new 8-page document details the construction procedure for a Mariotte siphon constant head infiltrometer using readily available materials. Written by Mahesh Bashyal, Michael J. Mulvaney, and Eban Z. Bean, and published by the UF/IFAS Agronomy Department, June 2019. http://edis.ifas.ufl.edu/ag433